A comparative analysis of selected pizza parlor chains delivery service towards customer satisfaction - Alingalan,Cassandra Jae M. Alvez, Kimberly Leigh A. Castillo, Jhamila Miccae I. Catacutan, Almar Joshua B. and Ruby, Jean Angelica C. 4 0 16; 5 (2016)
u
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila 2016.
Keywords: 2 -- 0; 6; 20; 20; 2